Leopardi and Finlayson (Iter, 2022)
Abanando Roapresents us a lucid essayabout Leopardian influence on Clarence Finlayson, a Chileanphilosopherfrom the first halfofthe XX century; in love with the poetryhe regarded as “reflective experience ofpoetizing ”. In spite ofdifferences- Finlayson, opposed to Leopardi, was afervent believer- both menfeltthat poetry and philosophy are “extremes which are dealt with in thesame contení”. Finlayson sensed in Leopardi “a denial of onthologicnature which, though a negative way; can lead to a new perception o fbeing ” and maintained that his pesimism wasn 't but “nostalgia o f therevelation of being itself\ Roa concludes that Finalyson and Leopardi“sought the same, although in opposite ways they were both “pilgrimsof the absolute ”.